IMPACT OF IMPLEMENTING INFORMATION TECHNOLOGY ON TEACHING IN PUBLIC SECONDARY SCHOOLS IN MBEERE SUB-COUNTY, EMBU COUNTY, KENYA - Murungi, Verasia Mukwaiti; Kibaara, Dr. Tarsilla M.; Mwaniki, Terry M. (IJRDO- Journal of Educational Research, 2017)
The significant role of information and communication technology (ICT) in education has been improving and the Kenyan Government has developed policies and initiatives to institute the use of ICT’s in schools and this study therefore sought to establish the impact of implementing information technology on teaching in public secondary schools by examining the impact of ICT in teaching. The findings of the study showed that although the government established ICT policies to enhance use of ICT, secondary schools in the Sub County have not adequately implemented ICT in teaching, with the study showing that teachers lacked the necessary skills for the ICT uptake, though the they have the will and commitment to roll out the ICT policy as directed by the Ministry. The study recommends that teachers need to be supported through training on ICT skills necessary for teaching, and that computer applications to form part of the teacher training curriculum.